Model‐based simulation to support the approval of isatuximab alone or with dexamethasone for the treatment of relapsed/refractory multiple myeloma in Japanese patients - Hoai‐Thu Thai; Kimiko Koiwai; Yoshihisa Shitara; Hirotaka Kazama; Jean‐Baptiste Fau; Dorothée Semiond; Christine Veyrat‐Follet (Wiley, 2023)
Abstract This study aimed to support dosing regimen selection for isatuximab as a single agent or in combination with dexamethasone for Japanese patients with relapsed/refractory multiple myeloma (RRMM). A joint model characterizing the dynamics of serum M‐protein kinetics and its association with progression‐free survival (PFS) was developed using data from 201 evaluable Japanese and non‐Japanese patients with RRMM enrolled in two monotherapy phase I/II trials, where Japanese patients (n = 31) received isatuximab at 10 or 20 mg/kg once weekly (qw) for 4 weeks then every 2 weeks (q2w) in subsequent cycles (10 or 20 mg/kg qw-q2w). Among non‐Japanese patients, 38 received isatuximab 20 mg/kg qw-q2w in combination with dexamethasone. Trial simulations were then performed to evaluate the effect of the isatuximab dosing regimens on both serum M‐protein and PFS with and without dexamethasone. The model identified instantaneous changes in serum M‐protein as the best on‐treatment predictor for PFS. Trial simulations demonstrated that 20 mg/kg qw-q2w induced a greater decrease (30% vs. 22%) of serum M‐protein at week 8 and prolonged median PFS by 2.4 weeks compared with 10 mg/kg qw-q2w. Although Japanese patients did not receive isatuximab plus dexamethasone in the phase I/II trial, simulations predicted that isatuximab 20 mg/kg qw-q2w plus dexamethasone would induce a greater decrease (67% vs. 43%) of serum M‐protein and a prolonged median PFS by 7.2 weeks compared with isatuximab alone. Trial simulations support the approved isatuximab 20 mg/kg qw-q2w regimen when administered as a single agent and in combination with dexamethasone in Japanese patients.